Submucous Myoma Induces Uterine Inversion - Yu-Li Chen; Chi-An Chen; Wen-Fang Cheng; Chia-Yen Huang; Chih-Yuan Chang; Chien-Nan Lee; Chang-Yao Hsieh (Elsevier, 2006)
Objective: Inversion of the uterus is indeed a rarity for a gynecologist. The puerperal variety is associated with pregnancy, including term pregnancy and abortion. The nonpuerperal condition may be tumor-induced or idiopathic. We present a nonpuerperal uterine inversion and discuss a reasonable plan for its management Case Report: A 42-year-old, unmarried woman without sexual experience and any systemic diseases noted a mass outside of the vaginal introitus combined with massive vaginal bleeding and abdominal pain of sudden onset after taking laxative agents for colonoscopic preparation. Then she had voiding difficulty with distended bladder. A suprapubic urinary catheter was inserted and 800 mL urine was drained out. The patient received emergency tumor resection and subtotal hysterectomy. The diagnosis of uterine inversion was confirmed during operation. The postoperative course was uneventful and she was discharged without complication. Conclusion: Nonpuerperal inversion of the uterus is rarely encountered by gynecologists. Diagnosis of uterine inversion is often not easy and imaging studies might be helpful. Surgical treatment is the method of choice in nonpuerperal uterine inversion.